The nutrition needs of adolescent athletes: A systematic review - Awang Firmansyah; Muhammad Reza Aziz Prasetya (Universitas Nusantara PGRI Kediri, 2021)
Athletes certainly need better nutrition than ordinary people. These nutritional needs, especially for adolescent athletes, are very important as a supplement to produce performance, energy, growth, and in the recovery process. The purpose of this article is to explain the components or aspects that must be considered in meeting the nutritional needs of adolescent athletes. This study followed the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) and the Meta-analysis. There are scientific articles obtained from Elsevier, Pubmed, Science Direct, Web of Science, National Index, Google Scholar, Journal of Sport Nutrition. Some important aspects of meeting nutritional needs for adolescent athletes are as follows: calorie needs, macronutrients hydration, and timing. The analysis structure used in this study is in line with several bibliometric studies conducted on other topics. Research on nutrition in adolescent athletes, research on important aspects of nutrition to meet the needs of adolescent athletes, English and Indonesian articles, full text form, published from 2015 to 2021. Exclusion criteria, abstract only, unpublished articles in scientific journals. All aspects of fulfilling nutrition for adolescent athletes are very important to support performance and quality, especially for adolescent athletes.